IMPROVEMENT OF THE METHODS OF ALLOCATION OF OVERHEADS IN THE ACCOUNTING SYSTEM OF COSTS OF THE ENTERPRISE - Dziuba, V. I. (Science and Transport Progress, 2004)
A research has been proposed of permanent and variable portions of the factory costs in a transport enterprise, at their distribution in the general structure of expenditures.